RIPK1 and death receptor signaling drive biliary damage and early liver tumorigenesis in mice with chronic hepatobiliary injury - Subramanian, Santosh Krishna; Schirmacher, Peter (Cell death and differentiation, 2019)
Hepatocyte apoptosis is intrinsically linked to chronic liver disease and hepatocarcinogenesis. Conversely, necroptosis of hepatocytes and other liver cell types and its relevance for liver disease is debated. Using liver parenchymal cell (LPC)-specific TGF-beta-activated kinase 1 (TAK1)-deficient (TAK1LPC-KO) mice, which exhibit spontaneous hepatocellular and biliary damage, hepatitis, and early hepatocarcinogenesis, we have investigated the contribution of apoptosis and necroptosis in hepatocyte and cholangiocyte death and their impact on liver disease progression. Here, we provide in vivo evidence showing that TAK1-deficient cholangiocytes undergo spontaneous necroptosis induced primarily by TNFR1 and dependent on RIPK1 kinase activity, RIPK3, and NEMO. In contrast, TAK1-deficient hepatocytes die by FADD-dependent apoptosis, which is not significantly inhibited by LPC-specific RIPK1 deficiency, inhibition of RIPK1 kinase activity, RIPK3 deficiency or combined LPC-specific deletion of TNFR1, TRAILR, and Fas. Accordingly, normal mouse cholangiocytes can undergo necroptosis, while primary hepatocytes are resistant to it and die exclusively by apoptosis upon treatment with cell death-inducing stimuli in vitro, likely due to the differential expression of RIPK3. Interestingly, the genetic modifications that conferred protection from biliary damage also prevented the spontaneous lethality that was often observed in TAK1LPC-KO mice. In the presence of chronic hepatocyte apoptosis, preventing biliary damage delayed but did not avert hepatocarcinogenesis. On the contrary, inhibition of hepatocyte apoptosis fully prevented liver tumorigenesis even in mice with extensive biliary damage. Altogether, our results suggest that using RIPK1 kinase activity inhibitors could be therapeutically useful for cholestatic liver disease patients.